2019
DOI: 10.1021/acs.inorgchem.9b02274
|View full text |Cite
|
Sign up to set email alerts
|

Chelating and Bridging Roles of 2-(2-Pyridyl)benzimidazole and Bis(diphenylphosphino)acetylene in Stabilizing a Cyclic Tetranuclear Platinum(II) Complex

Abstract: The reaction of complex [Pt(Me)(DMSO)(pbz)], 1, (pbz = 2-(2-pyridyl)benzimidazolate) with [PtMe(Cl)(DMSO)2], B, followed by addition of bis(diphenylphosphino)acetylene (dppac), gave the novel tetranuclear platinum complex [Pt4Me4(µ-dppac)2(pbz)2Cl2], 2, bearing both the pbz and dppac ligands. In this structure, the pbz ligands act as both chelating and bridging to stabilize the tetraplatinum framework. The tetranuclear Pt(II) complex was fully characterized by NMR spectroscopy, X-ray crystallography and mass s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…On the other hand, two elementary reactions, oxidative addition and reductive elimination, are very important because of their major role in many catalytic processes. These reactions have been the subject of many studies, and organoplatinum­(II) and -(IV) complexes have been used to investigate their chemistry in detail. Most organoplatinum complexes used in this regard include N-donor (such as 2,2′-bipyridine) or cyclometalated (such as 2-phenylpyridinate) chelate ligands. These organoplatinum­(II) complexes having N^N or C^N ligands are highly reactive toward oxidative addition reactions, which typically proceed by an S N 2 mechanism, as has been confirmed experimentally and computationally. In contrast to many reports on the oxidative addition and reductive elimination of organoplatinum complexes bearing N^N or C^N chelate ligands, few studies have been reported on the reactivity of bis-NHC platinum complexes. , Bis-NHC chelate complexes of dimethylplatinum are rare. Jamali and co-workers prepared the complex [PtMe 2 (bis-NHC)] by the reaction of [PtMe 2 (μ-SMe 2 )] 2 with 1,1′-methylene-3,3′-bis­[( N -( tert -butyl)­imidazol-2-diylidene] in the presence of Ag 2 O .…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, two elementary reactions, oxidative addition and reductive elimination, are very important because of their major role in many catalytic processes. These reactions have been the subject of many studies, and organoplatinum­(II) and -(IV) complexes have been used to investigate their chemistry in detail. Most organoplatinum complexes used in this regard include N-donor (such as 2,2′-bipyridine) or cyclometalated (such as 2-phenylpyridinate) chelate ligands. These organoplatinum­(II) complexes having N^N or C^N ligands are highly reactive toward oxidative addition reactions, which typically proceed by an S N 2 mechanism, as has been confirmed experimentally and computationally. In contrast to many reports on the oxidative addition and reductive elimination of organoplatinum complexes bearing N^N or C^N chelate ligands, few studies have been reported on the reactivity of bis-NHC platinum complexes. , Bis-NHC chelate complexes of dimethylplatinum are rare. Jamali and co-workers prepared the complex [PtMe 2 (bis-NHC)] by the reaction of [PtMe 2 (μ-SMe 2 )] 2 with 1,1′-methylene-3,3′-bis­[( N -( tert -butyl)­imidazol-2-diylidene] in the presence of Ag 2 O .…”
Section: Introductionmentioning
confidence: 99%
“…There has been and continues to be much interest to functionalize alkanes through selective C–H bond activation to obtain more valuable organic chemicals under mild conditions. There are many reports on C–H bond activation using transition-metal complexes. In this area, homogeneous catalytic systems bearing late transition metals such as palladium and platinum are particularly important. The study of direct C–H bond activation is often difficult, and as a result, C–H alkane activation is often investigated through the protonolysis of M–C bonds (i.e., the microscopic reverse of the activation step) in organometallic compounds such as methylplatinum­(II) complexes. …”
Section: Introductionmentioning
confidence: 99%
“…[27] Understanding the mechanism of these bond activations is an important area of research. Although cyclometalation reactions via C-H bond activation have been widely studied, and different classes of cycloplatinated and rollover cycloplatinated complexes have been synthesized, [31][32][33][34][35][36][37][38][39][40][41][42] a detailed investigation when both N-H and C-H bonds are available for activation has not been reported for platinum complexes and is limited to a few studies for Ir and Co complexes. [43][44][45] In the present study, 2-(2 0 -pyridyl)benzimidazole (Hpbz) is selected as the ligand with both C-H and N-H to investigate its reaction with a dimethylplatinum (II) complex, (PtMe 2 (DMSO) 2 ), 1, (DMSO = dimethyl sulfoxide).…”
mentioning
confidence: 99%